Study of the development of a floating Basic Health Unit for Amazonian riverside communities (Research, Society and Development, 2021)
In communities that form on the banks of rivers, the precarious collection and treatment of sewage compromises the quality of water resources, which is why the occurrence of high rates of diseases resulting from the lack of basic sanitation is common. Due to socioeconomic and environmental conditions, these populations are prone to chronic degenerative diseases such as diabetes and hypertension. In this context, it is relevant to carry out studies that seek alternatives in health and for riverside families. This work aimed to dimension a new model of Basic Health Unit (UBS) as an alternative for implementation in riverside communities in the Amazon, and to present the estimated cost of the project's initial investment. Through an exploratory research, a survey of the requirements for the elaboration of the project was carried out, considering the pertinent legislation and the applicable technical standards. As a result, the work presents the proposal of the UBS adapted in a small catamaran-type vessel, versatile in terms of raising and lowering river levels, with subsystems that provide autonomy for the provision of health and primary care services. The projected floating UBS will have a structure capable of providing various health and primary care services and the initial investment cost for its construction is R$ 123,270.00.